Model characteristics of water polo players' movements in the vertical position during competition - Bratusa, Z.; Matkovic, I.; Dopsaj, M. (Biomechanics and Medicine in Swimming IX, 2003)
INTRODUCTION: During a match, a water polo player spends approximately 63 % of the total time in vertical position (1). This indicates that vertical position, with the structure of technical-tactical activities derived from it, is the most dominant in comparison with other activities. The task of this research was to define model activities realized during a match by a player in vertical position. METHODS: By means of using video-taped matches, 10 players of international level were analyzed. The following characteristic activities were observed and the time was measured in: vertical position (tvert), duel (tduel) , arm up (tarm), basic position (near the opponent) (tbasic), passive position (farther from the opponent) (tpassive), and ball possession (tball). Variables were presented in % of the total time spent in vertical position for each quarter of the match separately. The results were subjected to multivariant statistical method MANOVA, and the differences between the observed variables in the function of quarters were established by the model of repeated measures 4x5 (2). RESULTS: There was a statistically significant difference in the observed variables in the function of the quarters of the game (F=12.081, p-level=0.000). Separate variables varied in the function of quarters (F=6.597, p-level=0.002), as between the % of the presence of the observed elements in the function of quarters (F=6.892, p-level=0.000). In its structure of elements of the game realized from vertical position, the 3rd quarter differed the most, and the position arm up (tarm) among the elements of the observed positions. In relation to % of the observed game elements of vertical position, the following were present: (tbasic) with 38.39 %, (tduel) with 25.21 %, (passive) with 24.18 %, (tball) with 8.68 %, (tarm) with 3.36 % out of the total time spent in vertical position. DISCUSSION: The results are the consequence of what happened during the game. The most stable elements (in relation to % of presence) were duel (tduel) and vertical basic poss. (tbasic), while defensive play, i.e. arm up position (tarm), was the most variable element. Considering the structure of motor activities and the time spent in vertical position, it is necessary to restructure the training in favor of the situation elements of the game. Future researches should define model characteristics of players` activities in vertical position in relation to various positions in a team on larger sample.